2014
DOI: 10.3892/mco.2014.480
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of osteopontin expression in breast cancer: A meta-analysis

Abstract: Osteopontin (OPN) has been implicated in tumor development and progression over the last few years. However, the prognostic value of OPN overexpression in patients with breast cancer remains controversial. We performed a meta-analysis to investigate the association of OPN expression in the tumor with the clinicopathological characteristics and survival of breast cancer patients. A total of 8 studies met the inclusion criteria and were entered in the meta-analysis. The data analysis demonstrated that OPN expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…Also We found that there were no association between osteopontin plasma level and age ,parity or menopausal status. This finding is concordant with Xu et al [4], in their meta-analysis study found that there was no correlation between OPN expression and age (P=0.572) and between OPN expression and menopausal status ( p=0.688). Moreover osteopontin plasma level showed no correlation with histological subtype of cancer (p=0.27).This result is in concordance with, Thorat et al, [7] who found that OPN expression didn't correlate with histological subtype of cancer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also We found that there were no association between osteopontin plasma level and age ,parity or menopausal status. This finding is concordant with Xu et al [4], in their meta-analysis study found that there was no correlation between OPN expression and age (P=0.572) and between OPN expression and menopausal status ( p=0.688). Moreover osteopontin plasma level showed no correlation with histological subtype of cancer (p=0.27).This result is in concordance with, Thorat et al, [7] who found that OPN expression didn't correlate with histological subtype of cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The gene encoding OPN known as secreted phosphoprotein 1 (SPP1) is mapped to chromosome 4q24-q25. OPN is implicated in physiological as well as pathological processes ,It is expressed and secreted by various cells, and plays a role in bone remodeling, reconfiguration of tissue integrity during inflammatory processes, coronary stenosis, and cancer metastasis [4]. It has been demonstrated that OPN is associated with more than 30 cancers so far and a marker for breast, cervical, colorectal, head and neck, liver, lung, ovarian and prostate cancers, as well as for sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al showed that OPN expression was a predictor for poor overall survival and disease-free survival in breast cancer patients [31]. Zhao et al found that OPN expression was higher in patients with high-grade glioma than patients with low grade glioma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that PC3 CD133+ cells showed higher expression of OPN than DU145 CD133+ cells, suggesting that OPN elicits essential biological functions and may play a critical role of osteosclerosis during PC metastasis to bone. (40,41) OPN, also called secreted phosphoprotein 1 (SPP1), was initially identified as an extracellular matrix protein that inhibited formation and growth of hydroxyapatite crystals within the bone matrix and other organs. (42) Osteoblasts are the major source of OPN in bone tissue.…”
Section: Discussionmentioning
confidence: 99%